CARDIOVASCULAR AND OTHER NON-COMMUNICABLE DISEASES IN THE COUNTRIES OF THE NORTHERN DIMENSION PARTNERSHIP IN PUBLIC HEALTH AND SOCIAL WELL-BEING: PRIORITIES AND BETTER PREVENTION APPROACHES - G. Ya. Maslennikova; R. G. Oganov (Кардиоваскулярная терапия и профилактика)
The issues on prevention of non-communicable diseases (NCD) with the goal of premature mortality decrease and, respectively, of people lives saving, is being discussed actively in the countries of Northern Dimension Partnership in Public Health and Social Well-being (NDPHS). Comparative analysis of NCD in the NDP countries showed serious, approximately 3 times, differences in the parameters of premature mortality from NCD within the countries, and direct relationship of premature mortality from NCD with smoking prevalence in men, as with alcohol consumption in both sexes. Negative correlation is found in premature NCD mortality indices and amount of money spent on public health per person per year; such difference is as high as 10-15 times among the countries. The discussion of priorities and effective methods of NCD prevention by the members of NDPHS is significant for experience exchange and facilitates implementation of three strategies on NCD prevention and their promotion in all political and strategic events in the countries.